2007
DOI: 10.1007/s10681-007-9541-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of stem rust resistance in the spring wheat cultivar Thatcher and the enhancement of stem rust resistance by Lr34

Abstract: Three recombinant inbred line populations from the crosses RL6071/Thatcher, RL6071/ RL6058 (Thatcher Lr34), and Thatcher/RL6058, were used to study the genetics of stem rust resistance in Thatcher and TcLr34. Segregation of stem rust response in each population was used to determine the number of genes conferring resistance, as well as the eVect of the leaf rust resistance gene Lr34 on stem rust resistance. The relationship between resistance in seedling and adult plants was also examined, and an attempt was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…However, transfer of Lr34 into Thatcher results in the expression of effective stem rust resistance possibly through interaction of Lr34 with unlinked Thatcher genes. There is good evidence that the ‘enhancement effect’ of Lr34 on stem rust resistance is race specific suggesting that the mode of action is different to the race non-specific response conferred by this gene against leaf rust and stripe rust [11,12,14]. This study has confirmed that Lr67 is also associated with enhanced stem rust resistance in Thatcher.…”
Section: Discussionsupporting
confidence: 62%
“…However, transfer of Lr34 into Thatcher results in the expression of effective stem rust resistance possibly through interaction of Lr34 with unlinked Thatcher genes. There is good evidence that the ‘enhancement effect’ of Lr34 on stem rust resistance is race specific suggesting that the mode of action is different to the race non-specific response conferred by this gene against leaf rust and stripe rust [11,12,14]. This study has confirmed that Lr67 is also associated with enhanced stem rust resistance in Thatcher.…”
Section: Discussionsupporting
confidence: 62%
“…Previous reports showed that the combination of Lr34 with additional genes from ‘Thatcher’ can contribute to enhanced stem rust resistance under field conditions [ 12 , 26 ]. Here, we have quantified possible interactions by examining the effect of Lr34 on Sr12 at the seedling stage.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also examined the interactions between Lr34 and Sr genes found in ‘Thatcher’. One study suggested that Sr16 and Sr12 may have contributed to resistance of adult plants in their ‘Thatcher’-derived population but focused on resistance associated with markers on chromosome arm 2BL [ 26 ]. In a follow-up study, a QTL was identified in ‘Thatcher’ on chromosome arm 2BL that was enhanced by Lr34 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are several cases of resistance genes that do not show the same phenotype in parental varieties as compared to their progenies. Understanding this phenomenon was required in order identify the suppressor of the Lr34 leaf rust resistance gene in wheat (Vanegas et al, 2008). In another case, the Lr13 leaf rust resistance gene is known to enhance resistance only in the presence of Lr17 (Kolmer, 1992).…”
Section: Genetical Genomics Offers New Horizons To Investigate Plant mentioning
confidence: 99%